Analysis of operation environment influence of 1.8 GHz TDD-LTE industry private network - Tao DU; Xiaohui DENG; Gang LI (Dianxin kexue)
According to current spectrum regulation,band 1 785～1 805 MHz is the only authorized wireless broadband spectrum.For most industry private network bearer business is directly related to safety production,it is necessary to analyze the running environment of the wireless spectrum operation.According to the planning of the 3GPP band and Band3 FDD-LTE band adjacent,it is necessary to analyze whether the Band3 frequency band interferes with the 1.8 GHz TDD-LTE private network.Based on the relevant frequency policies and model approval issued by the current state,the interference between the base stations was analyzed and suggestions for the relevant model approval documents were made.